1996
DOI: 10.1074/jbc.271.22.13169
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Inactivates Cellular Protein Kinase Cα

Abstract: Ceramide mediates the effects of extracellular agents on cellular growth, differentiation and apoptosis. In this study, we explored the mechanisms by which ceramide induces its cellular effects. In Molt-4 cells, phorbol 12-myristate 13-acetate (PMA) induced retinoblastoma gene product (Rb) phosphorylation, and ceramide inhibited this effect, suggesting an inhibitory effect of ceramide on the protein kinase C (PKC) pathway, the primary target of PMA. Molt-4 cells contained primarily PKCalpha and betaII isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
160
3
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(172 citation statements)
references
References 38 publications
7
160
3
2
Order By: Relevance
“…Furthermore, these results also concur with the observation that inhibition of PP2A leads to down-regulation of TCR expression (9). It has been reported that ceramide inactivates cellular PKC␣, and it could be speculated that the observed TCR up-regulation could be caused by an inhibition of PKC activity (31). However, inhibition of PKC␣ was first observed following 4.5-h incubation with ceramide and could thus not explain the rapid TCR up-regulation observed in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, these results also concur with the observation that inhibition of PP2A leads to down-regulation of TCR expression (9). It has been reported that ceramide inactivates cellular PKC␣, and it could be speculated that the observed TCR up-regulation could be caused by an inhibition of PKC activity (31). However, inhibition of PKC␣ was first observed following 4.5-h incubation with ceramide and could thus not explain the rapid TCR up-regulation observed in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…It is of particular interest that the apoptosis inducer ceramide can activate protein phosphatase 2A (Dobrowsky et al, 1993) and has been reported to induce the dephosphorylation and inactivation of PKCa (Lee et al, 1996). While it remains to be established in this context whether inactivation of PKCa is a necessary component of the ceramide induced apoptotic response, the data here suggest that this inactivation may indeed be critical.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, the literature suggests that PKC-a has a predominantly antiapoptotic role (Deacon et al, 1997). For example, PKC-a is inhibited during ceramide-induced apoptosis (Lee et al, 1996) and expression of a dominant-negative PKC-a induced apoptosis in CHO cells (Whelan and Parker, 1998). Thus, those bile acids known to promote cell proliferation and inhibit butyrate-induced apoptosis, that is, UDCA, CDCA and DCA (Mahmoud et al, 1999;McMillan et al, 2000), are likely to be mediated by the activation of PKC-a.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to apoptosis, PKC-a and -bll appear to be antiapoptotic in most cells. PKC-a is inactivated by proapoptotic factors including ceramide (Lee et al, 1996) and is known to phosphorylate bcl-2, potentiating its antiapoptotic function in mitochondria (Ruvolo et al, 1998). PKC-bll is a mitotic lamin kinase (Goss et al, 1994) involved in the regulation of proliferation.…”
mentioning
confidence: 99%